2003
DOI: 10.1002/neu.10285
|View full text |Cite
|
Sign up to set email alerts
|

Myosin function in nervous and sensory systems

Abstract: Development of the nervous system requires remarkable changes in cell structure that are dependent upon the cytoskeleton. The importance of specific components of the neuronal cytoskeleton, such as microtubules and neurofilaments, to neuronal function and development has been well established. Recently, increasing focus has been put on understanding the functional role of the actin cytoskeleton in neurons. Important modulators of the actin cytoskeleton are the large family of myosins, many of which (classes I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 123 publications
(138 reference statements)
1
55
0
Order By: Relevance
“…No mutations of this gene have been reported in Drosophila. However, the role of nonmuscle myosins in the embryonic development of the nervous system has been described extensively in rodents (24). RNAi-dependent suppression of Mhcl gene function resulted in loss of neurons and disorganization of the VNC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No mutations of this gene have been reported in Drosophila. However, the role of nonmuscle myosins in the embryonic development of the nervous system has been described extensively in rodents (24). RNAi-dependent suppression of Mhcl gene function resulted in loss of neurons and disorganization of the VNC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the LH surge, we showed up the overexpression of several neuronal-related genes such as THBS1 (Liauw et al 2008), FGF2 (Chen et al 2010), MYO1D (Brown & Bridgman 2004), SYNPO (Vlachos et al 2009), and CD9 (Ishibashi et al 2004;Figs 2 and 4). Strikingly, the common functions ensured by these genes were mainly neuron plasticity, neurogenesis (including the dendrogenesis and the axogenesis), and synaptogenesis.…”
Section: Neuronal-like Functions Of Cumulus Cellsmentioning
confidence: 99%
“…It is widely known that CCs-oocyte communications occurred mainly through the gap junctions (Szollosi 1978, Carabatsos et al 2000. These communications played important roles in the oocyte-somatic compartment cell signaling and decreased at the GVBD (Sutovsky et al 1993, Mattioli & Barboni 2000.…”
Section: Cell Signalingmentioning
confidence: 99%
“…Nonmuscle Myosin II, a hexameric protein complex found in all cell types, is a molecular motor that dramatically regulates actin dynamics in growth structures (Lin et al 1996;Brown and Bridgman 2004;Medeiros et al 2006). Recently, our group reported that theta stimulation activates synaptic Myosin II motor force generation in the hippocampus which, in turn, promotes spine F-actin polymerization (Rex et al 2010).…”
mentioning
confidence: 99%